Associations of altered hepatic gene expression in American lifestyle-induced obesity syndrome diet-fed mice with metabolic changes during NAFLD development and progression - Iannone Valeria; Lok Johnson; Babu Ambrin Farizah; Gómez-Gallego Carlos; Willman Roosa Maria; Koistinen Ville Mikael; Klåvus Anton; Kettunen Mikko I; Kårlund Anna; Schwab Ursula; Hanhineva Kati; Kolehmainen Marjukka; et al. (Elsevier Inc., 2025)
Non-alcoholic fatty liver disease (NAFLD) pathogenesis remains poorly understood due to the complex metabolic and inflammatory changes in the liver. This study aimed to elucidate hepatic events related to inflammation and lipid metabolism and their linkage with metabolic alterations during NAFLD in American lifestyle-induced obesity syndrome (ALIOS) diet-fed mice. Forty-eight C57BL/6J male mice were fed with ALIOS diet (n=24) or control chow diet (n=24) for 8, 12, and 16 weeks. At the end of each timepoint, eight mice were sacrificed where plasma and liver were collected. Hepatic fat accumulation was followed using magnetic resonance imaging and confirmed with histology. Further, targeted gene expression and non-targeted metabolomics analysis were conducted. Our results showed higher hepatic steatosis, body weight, energy consumption, and liver mass in ALIOS diet-fed mice compared to control mice. ALIOS diet altered expression of genes related to inflammation (Tnfa and IL-6) and lipid metabolism (Cd36, Fasn, Scd1, Cpt1a, and Ppara). Metabolomics analysis indicated decrease of lipids containing polyunsaturated fatty acids such as LPE(20:5) and LPC(20:5) with increase of other lipid species such as LPI(16:0) and LPC(16:2) and peptides such as alanyl-phenylalanine and glutamyl-arginine. We further observed novel correlations between different metabolites including sphingolipid, lysophospholipids, peptides, and bile acid with inflammation, lipid uptake and synthesis. Together with the reduction of antioxidant metabolites and gut microbiota-derived metabolites contribute to NAFLD development and progression. The combination of non-targeted metabolomics with gene expression in future studies can further identify key metabolic routes during NAFLD which could be the targets of potential novel therapeutics.